Peningkatakan Keterampilan Menulis Teks Deskripsi Menggunakan Model Contextual Teaching and Learning (CTL) di Kelas V SD Negeri 07 Pasaman Kabupaten Pasaman Barat - Annisa, Fatimah Azzikri; Sukma, Elfia (Indo-MathEdu Intellectuals Journal, 2025)
This research is motivated by the less optimal implementation of descriptive text writing activities in learning which has an impact on the low writing ability of students in class V of SD Negeri 07 Pasaman, West Pasaman Regency. This study aims to describe the planning, implementation and improvement of descriptive text writing skills using the Contextual Teaching and Learning (CTL) model in grade V of SD Negeri 07 Pasaman, West Pasaman Regency. This type of research is Classroom Action Research (PTK). This research was carried out in 2 cycles with the stages of planning, implementation, observation and reflection. Data is collected through test and non-test techniques while research instruments are through test sheets and non-tests. The data was analyzed using the percentage formula. The results of the study showed that the average value for teacher and student activities in cycle 1 of meetings 1 and 2 was 86.25 with a good qualification (B). Then in cycle II, scores were obtained for teacher activities of 95 and student activities of 95 with very good qualifications (A). So that the success rate of the implementation of writing learning in descriptive texts using the Contextual Teaching and Learning (CTL) model in grade V of SD Negeri 07 Pasaman, West Pasaman Regency is included in the category of very good because it has increased.